Perceptions of Pre-Service PPG Students Towards The Implementation of the Hybrid Learning PPG Program at University of Palangka Raya - Artuti, Emy; Pinardi, Janu; Azahari, Abdul Rahman; Basuki, Bejo; Ratnawati, Oktaviana Ainun (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
The purpose of this study was to determine the perceptions of Pre-service PPG students regarding the implementation of the PPG hybrid Learning program at Palangka Raya University in 2024. This research uses descriptive research with quantitative and qualitative approaches with survey research type. The population in this study were all PPG Pre-service students totaling 133 people. Data collection techniques by distributing questionnaires consisting of closed and open questionnaires. Before being used, the questionnaire was first validated and obtained a value of V = 0.86> 0.8 including the high category and the reliability test obtained a value of PA = 91%> 75% including the good category and feasible to use. The results showed that the perceptions of Pre-service PPG students towards the implementation of the PPG Hybrid Learning program at Palangka Raya University were obtained in the aspects of learning implementation, learning activities and learning completeness were included in the very good category, this can be seen from the questionnaire results where students who answered agree and strongly agree reached more than 80%, some even more than 90%. Whereas in the aspect of lecture halls and learning facilities, it is still included in the insufficient category, especially in the statement about the facilities provided by the campus being adequate in the implementation of hybrid learning, this can be seen from the results of the student questionnaire who answered agree and strongly agree only reached 35%, which means there are still around 65% of students who answered disagree and disagree in the questionnaire given. Keywords: student perception, pre-servive ppg, hybrid learning